Penerapan Manajemen Pengendalian Persediaan Bahan Baku dengan Metode EOQ dan POQ di Perumda Perkebunan Kahyangan Jember - Katherine, Nadila Maosi; Wardhana, Danu Indra; Setiawan, Andika Putra (CV. Lentera Literasi Indonesia, 2025)
The management of ground coffee raw materials at PERUMDA Perkebunan Kahyangan Jember is still conducted conventionally, resulting in shortages and excess inventory, which negatively affect the company's production and finances. This study aims to: (1) Analyze the impact of the Economic Order Quantity (EOQ) method on total storage costs, (2) Analyze the effect of the Period Order Quantity (POQ) method on total storage costs, and (3) Identify factors affecting raw material availability. The research employs descriptive analysis with a quantitative approach, collecting primary and secondary data related to ordering, usage, and storage costs of ground coffee raw materials in 2023, and using Ishikawa diagrams to identify causes of shortages. Results show that the EOQ method yields an optimal order quantity of 5,751 kg with an order frequency of 8 times a year and a total inventory cost of Rp. 502,787. Conversely, the POQ method results in a higher order frequency of 11 times, with a total inventory cost of Rp. 3,671,407. Thus, the EOQ method is concluded to be more efficient in controlling inventory costs compared to the POQ method.